Status of agricultural water management practices in Africa: a review for the prioritisation and operationalisation of the Africa Union’s irrigation development and agricultural water management (AU-IDAWM) strategy - Dirwai, Tinashe Lindel; Taguta, C.; Senzanje, A.; Nhamo, L.; Cofie, Olufunke O.; Lankford, B.; Nyambe, H. N.; Mabhaudhi, T. (IOP Publishing, 2024)
Efficient agricultural water management (AWM) practices enhance crop water productivity and promote climate change adaptation and resilience initiatives, particularly in smallholder farming systems. Approximately 90% of sub-Saharan Africa’s (SSA) agriculture is rainfed under smallholder farmers who constitute about 60% of the continent’s population and depend on agriculture for their livelihoods. While AWM is central to the African agenda, knowledge of AWM is fragmented, making it challenging to operationalize regional initiatives at country levels. Therefore, this study sought to review the status of AWM practices and technologies in Africa and provide guidelines, scenarios, and investment plans to guide the prioritization and operationalization of the African Union’s irrigation development and AWM (AU-IDAWM) initiative. The initiative proposes four developmental pathways; 1—improved water control and watershed management in rain-fed farming, 2—farmer-led irrigation, 3—irrigation scheme development and modernization, and 4—unconventional water use for irrigation. The preferred reporting items for systematic reviews and meta-analyses approach guided the systematic literature review. The study indicates that most agricultural production systems are mainly under pathways 1 and 2, which dictate the subsequent AWM practices. Pathway 4 had isolated adoption in North Africa. SSA exhibited overlaps in opportunities for AWM, whereas North Africa had green energy and strong extension services. The challenges were unique to each geopolitical region. Policy-related issues affected North Africa, whilst low investment in AWM dominated West Africa. Poor institutional coordination plagued East Africa, whilst low access to extension services affected Southern Africa. The Central African region was undermined by poor management practices that culminated in soil salinity in the agricultural lands. Targeted and scalable investments across interventions are necessary to potentially improve AWM uptake and subsequent food security in the continent. Also, institutional setups are essential in coordinating efforts towards achieving AWM. Extension services are essential information dissemination platforms for adopting effective climate-smart agriculture.